(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To define the epidemiological profile of patients with chronic wounds treated by the Multidisciplinary Home Care Team (EMAD) of Rio Branco, state of Acre. Methods: This is an exploratory, field study, in which users were enrolled in the Better at Home Program from January to May 2018. The sample of this study was composed of all active patients in the list attended by EMAD in the period comprised from the first visit of the researchers until the moment of exhaustion of the patients for the data collection. All patients of EMAD with wounds were included, totaling the sample of 100 patients. Results: One hundred patients answered a self-administered questionnaire. It was shown that 54% of the participants were men, with age greater than 51 years and mean age of 50 years [standard deviation (SD) = 19.81]. Sixty percent were brown, 36% singles, 52% had income between one and two minimum wages, 34% had incomplete elementary education, and 35% were retired. Of those selected, 80% live in their properties, 70% of which is masonry, water is piped in 74% of the places, and 100% has electricity. About 38% had hypertension, and 31% were diabetic, being the most prevalent diseases. Families were the main responsible for patients’ access to home care (45%). Lower limb injuries were the most prevalent (38%). It was possible to observe a low level of schooling and income in these patients, besides the majority presence of chronic noncommunicable diseases, as well as the importance of families in the search for specialized treatment. Conclusion: For the quicker rehabilitation of the patients, a holistic view is necessary, relating all areas of health and using the interdisciplinary knowledge so that greater treatment effectiveness occurs.